The forgotten electrolyte, when hypercalcaemia manifest as gait instability and altered mental status. (5th March 2018) - Ugalde, Israel; Bello Segura, Manuel; Oneto, Sabrina; Ciment, Ari
Abstract : An altered mental status presents a diagnostic challenge for many clinicians. Described here is a case of primary hyperparathyroidism not initially suspected until after a thorough neurological and infectious cause were excluded. A 60-year-old woman presented with altered mental status and gait instability. Her family noticed progressive gait instability and mood swings for the past 4 months. Initial imaging and laboratory values were unable to explain her symptoms. On transfer out of the intensive care unit, her corrected calcium was found to be 13.3 mg/dL with an elevated parathyroid hormone. Her hypercalcaemia was refractory to medical management. Ultrasound found a 2 cm nodule, which was surgically removed and found to be a parathyroid adenoma. Her calcium normalised and neurological deficits subsided. Hypercalcaemia can lead to a constellation of symptoms that include the classical 'stones, bones, abdominal moans and psychic groans' and electrolyte derangements should be considered in the differential of altered mental status.